UMPSA, Hebei University sign collaboration to offer Dual Degree in Data Science and Big Data Technology - Siti Nur Azwin, Zulkapri (UMPSA, 2025)
KUANTAN, 24 June 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to strengthen its international collaboration with the signing of a Memorandum of Agreement (MoA) with Hebei University, China, for the implementation of a dual degree programme in Big Data Technology.